2013
DOI: 10.1021/jp307875z
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Amphiphilic Diblock Co-oligomers with Nonionic and Ionic Hydrophilic Groups

Abstract: The synthesis of a series of co-oligomer amphiphiles by RAFT and their self-assembly behavior in water is described. These novel amphiphiles, comprised of styrene, butyl acrylate, and alkyl hydrophobes together with ionic acrylic acid and nonionic hydroxyethylacrylate hydrophilic moieties and with a total degree of polymerization from 5 to 17, represent a new class of small-molecule surfactants that can be formed from the immense potential library of all polymerizable monomers. Examples of micellar solutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 46 publications
(86 reference statements)
3
16
2
Order By: Relevance
“…Figure 2 shows the distribution of AA units for the first block (from ESI-MS) of about a mode of five AA units. Note that both the mass spectra and NMR results indicate a slightly longer average degree of polymerization for the AA block than in our previous study, 23 consistent with the polymerization The structure of synthesized co-oligomers after adding the second block was analyzed by 1 H NMR, yielding conversions of between 94 and 98% (Table 2). From the 1 H NMR spectra, each type of co-oligomer contained five carboxylic groups from five AA units (Materials and Methods) and the correspondingly desired second block.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 2 shows the distribution of AA units for the first block (from ESI-MS) of about a mode of five AA units. Note that both the mass spectra and NMR results indicate a slightly longer average degree of polymerization for the AA block than in our previous study, 23 consistent with the polymerization The structure of synthesized co-oligomers after adding the second block was analyzed by 1 H NMR, yielding conversions of between 94 and 98% (Table 2). From the 1 H NMR spectra, each type of co-oligomer contained five carboxylic groups from five AA units (Materials and Methods) and the correspondingly desired second block.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…Heinen et al focused on the phase behavior of amphiphilic diblock co-oligomers n-butyl acrylate-b-2-hydroxyethyl acrylate (BA 5 -b-HEA 5,6,7,8 ), styrene-bacrylic acid (S 5,9,12 -b-AA 5 ), and n-butyl acrylate-b-acrylic acid (BA 5,9,12 -b-AA 5 ) in aqueous solution. 23 Systems of BA 5 -b-HEA 5,6,7,8 are nonionic amphiphilic diblock co-oligomers, whereas both S 5,9,12 -b-AA 5 and BA 5,9,12 -b-AA 5 are ionic. Spherical micelles were found in BA 5 -b-HEA 5,6,7,8 , while both spheres and lamellar structures were formed in BA 5 -b-HEA 6,7,8 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same principle has been expanded and applied to miniemulsion polymerization, , encapsulation of solid particulates, and synthesis of anisotropic polystyrene particles. , Our miniemulsion work especially demonstrated the potential for employing diblock macro-RAFT of poly­(styrene)- block -poly­(acrylic) to generate hollow particles. However, further investigations found that the conditions for such clean and straight forward diblocks to self-assemble and generate desired structures in the aqueous phase proved to be quite complex . In this work, the ability to use amphiphilic diblock macro-RAFT copolymers in emulsion polymerization to spontaneously form polymeric vesicles at relatively high concentrations is explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, further investigations found that the conditions for such clean and straight forward diblocks to self-assemble and generate desired structures in the aqueous phase proved to be quite complex. 49 In this work, the ability to use amphiphilic diblock macro-RAFT copolymers in emulsion polymerization to spontaneously form polymeric vesicles at relatively high concentrations is explored. The uniquely designed macro-RAFT copolymers of RAFT-(styrene) z -block-[(acrylic acid) a -co-(butyl acrylate) b ] (see Figure 1) would be first employed as dispersants to emulsify styrene (Sty) monomer.…”
Section: ■ Introductionmentioning
confidence: 99%